Galectin-3 inhibits the chemotaxis of human polymorphonuclear neutrophils in vitro - Baseras, Billur; Gaida, Matthias; Kahle, Nadine; Schuppel, Ann-Kathrin; Kathrey, Diana; Prior, Birgit; Wente, Moritz N.; Hänsch, Gertrud Maria (Immunobiology, 2012)
In the recent years, the participation of the animal lectin galectin (gal)-3 in inflammation and in host defence mechanisms was extensively studied. In vivo studies implied – among others – a role of gal-3 in the recruitment of polymorphonuclear neutrophils (PMN) to sites of bacterial infection. In that context, we asked the question whether gal-3 was chemotactic for PMN. Functional assays revealed that gal-3 was not chemotactic for PMN, but that it inhibited the spontaneous migration and the chemotaxis of PMN towards complement C5a, interleukin (IL)-8, or ATP. Moreover, gal-3 inhibited the shape change and the actin polymerisation of PMN that occurs in response to C5a or IL-8. By use of FITC-labelled gal-3, we found that it attached rapidly to the PMN membrane in a lactose-sensitive manner. In response to gal-3 the MAP kinase p38 was phosphorylated. This kinase is crucial for the migration of PMN towards end-target chemokines, such as C5a, and is activated in response to C5a or IL-8. When PMN were preincubated with gal-3, the C5a-induced p38 phosphorylation was transiently enhanced, but eventually down-modulated. We conclude that by interfering with the chemokine-induced p38 phosphorylation gal-3 inhibits chemotaxis of PMN.
Available online 5 August 2011
Gesehen am 24.10.2018